Converting Carbon Dioxide in to Methane Gas and Enhance Oil Recovery by using Biotechnology Process - Ayyed, Abbas Kadhim (Journal of Petroleum Research and Studies, 2022)
Using biotechnology in petroleum industry has many advantages .for example , Microbiologically Enhanced Oil Recovery (MEOR) increase of the productivity of the oil field and decrease the viscosity of the crude oil . It's known that atmosphere has considerable amount of CO2 gas as a result of industrial activities (crude oil production). CO2 gas plays a role in increasing atmosphere temperature and causing global warming. Bioremediation is a viable Biotechnology function for Re-producing depleted wells and global warming. It means Bioremediation uses metabolic adaptation of microorganism, a promising approach, using this technique employs of Methanogenic bacteria to convert CO2 gas in to CH4. Therefore turns carbon dioxide in to carbon which is added to crude oil (so contribute decrease the viscosity for heavy crude oil, This mechanism is a part of the promotion of oil production.it is apart an operation EOR. and Second reacts with Hydrogen by Bacteria to produce methane gas. The aim study, advantage this method increase production. and removal global warming. In this review, we discuss the role of Methanogenic bacteria in transforming CO2 gas into methane gas , that it has a role in crude oil production . Methanogenic bacteria have an important role in petroleum industry and environment during decreasing CO2 amount in the atmosphere and increasing reservoir pressure. MEOR technology uses strains that have a role in crude oil production; these bacterial strains produce biogases (Methane) that increase reservoir pressure. In this study, six strains were isolated from Rumaila oilfield, south of Iraq. These strains were identified based on microscopic and morphological observations. These strains were Methanogenic bacteria. The main part of this study includes identification of bacteria that can consume CO2 gas and making continual lab experiments to isolate and determine the best genus to do this process in oil field. Experiments were done in specific bio-labs for two years, Methanogenic bacteria strains were isolated by using specific selective growth media. The second part of this study is using these strains for bioremediation process of oil wells, which includes providing anaerobic conditions for these strains to transform CO2 gas to methane . Morphological and microscopic observations were conducted to these strains and showed the best kind of these strains according to the ability of transformation of CO2 to methane. The isolated bacteria were called BRS11 strain showed high efficiency in transformation of CO2 to methane.